A STUDY ON QUALITY OF WORK LIFE OF DOCTORS WITH SPECIAL REFERENCE TO KANCHIPURAM DISTRICT - M, UmaRaman.; Priya, G. Shanmuga (International Journal of Psychosocial Rehabilitation, 2020)
Quality of Work life is an essential criterion for a favourable environment in any organisation. A doctor has a very important role in the modern society. Doctors in Higher Education sector can transform to patient cognition and intellectual dimensions. Doctors who perceive good quality of work life can develop and direct students and patient perception. The present study attempts to inquire into the quality of work life of Doctors working across different hospitals streams in different colleges in different administrative and organisational set up in Kancheepuram district. 250 Doctors from various administrative set up are selected for the study. The research found a positive and significant relationship between the age groups of doctors and various dimensions of quality of work life. The result and implications are discussed.